Hukuman Pidana Dalam Islam: Analisis Konseptual, Maqāṣid Asy-Syarī‘ah, Dan Relevansi Kontemporer - Maulida Hasanah; Muna Hasanah; Noormala Santi; Lahmudinur (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
Islamic criminal law, or fiqh jinayah, plays a crucial role within the religious legal framework that governs social life. Its primary purpose is to safeguard the five fundamental principles of the Sharia, namely the protection of religion, life, intellect, lineage, and property. This study aims to analyze the foundational concepts of punishment in Islam, including the categories of hudud, qisas-diyat, and ta’zir, while also examining how these legal concepts relate to contemporary legal systems. The research gap addressed in this study lies in the limited comprehensive analyses that integrate the perspective of maqasid al-shariah with constitutional challenges and human rights issues in contemporary Islamic criminal law discourse, particularly within Indonesian scholarship over the past five years. Therefore, this research offers novelty through an interpretative approach that combines normative-theological principles with an analytical examination of modern legal regulations. The sources examined include the Qur’an, Hadith, classical fiqh works, as well as academic literature and recent studies published between 2020 and 2025. The data were analyzed using content analysis and analytical comparison techniques, while data validation employed source triangulation by comparing scriptural texts, classical juristic opinions, and contemporary research findings. The results show that the implementation of Islamic criminal law today faces various challenges, especially those related to constitutional frameworks, legal pluralism, and human rights concerns. However, through an approach grounded in maqasid al-shariah and the principle of proportionality, Islamic criminal law can be reinterpreted to remain relevant, humane, and aligned with substantive justice.